Gestão por processos : uma análise da ferramenta de gestão utilizada para promover o alinhamento das estratégias organizacionais no poder judiciário de Santa Catarina - Domingues, Flavia de Martins Faria Vieira (2014)
Public administration must be guided by the basic principles such as impartiality, publicity and efficiency, so that their activities can always walk toward the public interest. In the course of public administration from patrimonial administration to new public management may be perceived progress in the professionalization of services. With the evolution of this scenario, the company began requiring increasingly, quality services, transparency of administrative acts and more effective results. Thus, public organizations have begun to review their structures and dynamics of operation, seeking to optimize their processes and work routines. Thus, identifying each worker process that runs in the organization, and seek their best performance, has become a means by which are eliminated unnecessary activities and seeks to better organizational performance. The objective here, undertaking empirical research and evidence relevant aspects diagnosed during phases of project management implementation processes in the judiciary of Santa Catarina. Thus, we sought to provide the future researchers, a theoretical synthesis compared with the results of the empirical field. Through semi-structured interviews and questionnaires, we sought to investigate the practice of the process of implementing the vision of planners and other actors involved in its design. This study was based on the view of the functionalist paradigm and how to approach the problem we chose a qualitative - quantitative research. It was evident that with the convergent use of the tools and techniques of process management, the servers began to rethink the way we work and perform activities. With the start of work orientation area, some servers began to see the processes in an integrated manner and to work cooperatively with other areas, seeking to change the departmental vision. However, the analysis of the data led to the understanding that resistance to change is significant, efforts are needed that encourage an organizational culture that has features that enhance aspects of functional integration, teamwork and continuous improvement of processes being. Finally, the study also pointed out as a result, the importance of effective communication, the need for a structure that supports the areas and the commitment of senior management and the people who will operate the processes.